Patent Portfolios and Competition Law: Some Reflections After the Recent RPSA Cases - Emanuela Arezzo (Market and Competition Law Review)
In the pharmaceutical sector, firms often build patent portfolios in order to better protect their innovations, but also to strategically exploit the cluster to prevent entry by generic competition. In fact, once patent protection on the main invention expires, originator firms adopt a two-tiered strategy, centred on the enforcement of secondary patents composing the portfolios. At first, originators threaten generic companies of patent infringement, in a way to discourage entry by generic companies. Secondly, they push generics to enter a patent settlement (in order to compose the very same infringement proceeding), often paying them to stay out of the market: hence, prolonging their exclusivity time, to the detriment of consumers and society at large. While EU institutions have made clear that the latter behaviour is in plain contrast with competition law provisions prohibiting agreements in restraint of trade, RPSAs are only the tail of a multifaceted conduct which deserves closer scrutiny.